Plug-and-Play Macroscopes. - BÖRNER, KATY (Communications of the ACM, 2011)
The article presents information on how to create macroscopes, software tools constructed from evolving software bundles which are said to be useful for analyzing scientific data. Macroscopes are named in contrast to microscopes, as they allow users to view information which would otherwise be too complex, slow, or large to be visible. The article describes how to use the service-oriented architecture Open Services Gateway Initiative (OSGi), and the open source software specification Cyberinfrastructure Shell (CIShell) to create plug-and-play macroscopes.